State-of-the-art on advanced technologies of solid-state circuit breaker for reliable and sustainable power supply: A bibliometric analysis and future guidelines - Roslan M.F.; Reza M.S.; Rahman M.S.; Mansor M.; Arsad A.Z.; Jern K.P.; Ramachandaramurthy V.K.; Hannan M.A. (Elsevier B.V., 2025)
This paper provides a comprehensive bibliometricanalysis of solid-state circuit breakers, including technological developments and control methods in electric power distribution systems. By compiling and analyzing data from the Scopus database, the most cited papers in the field of protection system mechanisms can be identified. These papers, published in influential journals from various countries, covered different subject areas and case studies. Notably, 77.64 % of the articles focused on technological development and experimental control methods, while 22.35 % were review-based studies. This underscores the increasing interest among researchers in advancing the sustainability and reliability of protection devices in electric power distribution systems. The paper aims to identify and analyze the highly cited published articles on the respective field to provide future research direction on the technological development and control methods towards solid-state circuit breaker protection devices. The review also underlines numerous factors, issues, challenges, and difficulties that next-generation power semiconductor should overcome with in regards to system sustainability. Thus, this analysis will strengthen the scopes and provide context for the development of technology and control in the main protection devices in order to achieve an efficient, reliable, cost-effective, and sustainable power supply. ? 2024